Development of E-Modules Oriented by A Science, Technology, Engineering, Art, and Mathematics (STEAM) Approach to Improve High Level Thinking Ability - Irza Rusni; Yanti Fitria; Syafri Ahmad; Zelhendri Zen (Jurnal Penelitian Pendidikan IPA, 2023)
Standards for 21st century learning for educators and students relate to the application of technology learning. One of the ways teachers use to optimize digital learning activities is by creating teaching materials in the form of e-modules. The aim of this research is to develop an electronic module oriented towards the STEAM learning approach. This e-module is used to improve elementary school students' high-level thinking abilities. This research uses the Research and Development research method with the ADDIE development model. The subjects of this research were grade IV elementary school students in Pariaman Tengah, Pariaman City, namely SDN 17 Kampung Baru, SDN 04 Rawang, and SDN 02 Karan Aur. There are three instruments for this research, namely validation instruments in the form of validation sheets, practicality instruments and effectiveness instruments. The results of this research areThe average validation result for the three aspects of media, language and material is 85.65, which is included in the very valid category. The paired sample t-test results were obtainedsignificance value of Sig. 0.000 <0.05so the data shows that there are differences significant difference between before using modules and afterwards, so it is stated that modules can increasing the high-level thinking abilities of high-class students